Does financial development mediate the impact of remittances on sustainable human capital investment? new insights from SSA countries - Bare, Uweis Abdulahi Ali; Bani, Yasmin; Ismail, Normaz Wana; Rosland, Anitha (Taylor and Francis Group, 2022)
Remittances play an important role in human capital development in sub-Saharan Africa, particularly when it comes to helping families to pay for their children’s education, access health care and alleviate poverty. However, many countries on the continent lack the financial systems to efficiently facilitate the inflows of remittances and allow them to be used to their greatest potential such as investment in education. The education of children is particularly essential if Saharan Africa is to achieve sustainable development goal number four which aims to ensure inclusive and quality education for all by 2030 . This paper examines the impact of remittances on human capital development from 1996–2016 in sub-Saharan Africa and further explores the role financial development in this established nexus. The empirical results revealed that remittances positively influence human capital investment, but when interacted with financial development and regressed on human capital investment, we found remittances impact to be more pronounced and statistically influence human capital. This study recommends that policymakers develop proactive policies that facilitate the inflows of remittances. Our policy suggestions are based on the fact that remittance recipients in SSA countries do not have adequate funds to invest in human capital because of weak financial systems. Financial market reform is therefore paramount for attracting greater remittances into SSA countries which, in turn, could be harnessed to ease credit constraints and allow for greater investment into human capital.